Intercritical photophobia in the migrainous patient. Proposal for diagnostic criteria - Ly-Yang, F.; Gómez-Calleja, V.; Pérez-García, P.; González-Gómez, N.; Porta-Etessam, J.; Santos-Bueso, E. (Neurología (Barcelona, English ed. ), 2023)
Photophobia is a symptom of abnormal light intolerance without pain sensation that requires an anamnesis and an examination to diagnose an underlying etiology. This article focuses on 30 clinical cases with isolated intense photophobia and on the review of the literature. The purpose of this article is to establish diagnostic criteria for photophobia. The etiology of photophobia appears to be at the level of the intrinsically photosensitive retinal ganglion cells known as melanopsin cells and at a neurochemical level mediated by calcitonin-related peptide and the pituitary activating peptide cyclase. The treatment of photophobia could consist of monoclonal antibodies against calcitonin-related peptide and/or pituitary activating peptide cyclase. La fotofobia es un síntoma de intolerancia anómala a la luz sin sensación de dolor que requiere de una anamnesis y una exploración para el diagnóstico de una etiología subyacente. El presente artículo se centra en 30 casos clínicos con fotofobia intensa aislada y su revisión de la bibliografía. El objetivo consiste en establecer unos criterios diagnósticos de la fotofobia. La etiología de la fotofobia parece encontrarse a nivel de las células ganglionares de la retina intrínsecamente fotosensibles, conocidas como las células de la melanopsina, y a un nivel neuroquímico mediado por el péptido relacionado con la calcitonina y el péptido pituitario activador de la ciclasa. El tratamiento de la fotofobia podría consistir en anticuerpos monoclonales contra los péptidos relacionados con la calcitonina y/o el péptido pituitario activador de la ciclasa.